IMPLEMENTASI PEMBIAYAAN SYARIAH DALAM LAYANAN ANIPAY MOBILE DI LEMBAGA KEUANGAN MIKRO SYARIAH BANGKALAN - A. Taufiq Buhari (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
This study examines the implementation of Sharia financing through the Anipay Mobile application at Islamic Microfinance Institutions (IMFIs) in Bangkalan Regency and evaluates its compliance with Sharia principles within the context of digital financial transformation. A qualitative case study approach was employed, with data collected through in-depth interviews involving IMFI managers, application developers, Sharia Supervisory Board members, and Anipay Mobile users, complemented by observation and documentation. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, while credibility was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that Anipay Mobile has enhanced the efficiency and accessibility of Sharia financing services by digitalizing financing applications, installment payments, transaction monitoring, and real-time financial information. The platform primarily facilitates mur?ba?ah financing, followed by wak?lah and ij?rah, whereas the implementation of profit-sharing contracts such as mu??rabah and mush?rakah remains limited due to challenges in business monitoring and profit-sharing calculations. From a Sharia perspective, the financing process fulfills the principles of transparency, contractual clarity, mutual consent, and freedom from rib?, gharar, and maysir. However, a hybrid mechanism combining digital transactions with manual verification is still applied for selected financing products to strengthen Sharia compliance and prudential practices. The study also identifies several challenges, including limited digital literacy among members, inadequate technological infrastructure, and the need to improve human resource competencies and Sharia governance. Overall, Anipay Mobile demonstrates strong potential as a digital innovation model capable of expanding Islamic financial inclusion, improving operational efficiency, supporting MSME empowerment, and advancing the objectives of Maq??id al-Shar??ah through transparent, effective, and sustainable Islamic financial services.